P-111 TAR (TRANSVERSUS ABDOMINIS MUSCLE RELEASE) AS AN ALTERNATIVE IN PATIENTS WITH INCISIONAL HERNIA AND COMPLEX ABDOMINAL WALL. ANALYSIS OF OUR EXPERIENCE. (13th October 2022) - Serrano Yébenes, E; Diaz Pedrero, R; Ovejero Merino, E; Córdova García, D M; Ratia Gimenez, T; Allaoua Moussasi, Y; Laguna Hernandez, P; Bru Aparicio, M; Manes Jimenez, F; Jimenez Martín, R; Medina Reinoso, C; San Román Romanillos, M R; et al.
Abstract: Aim: To analyze the results of patients with complex abdominal wall surgery using TAR(transversus abdominis muscle release) technique in our center. Material and Methods: An observational, descriptive, retrospective study of patients operated using TAR technique in a second level hospital in the last three years was carried out. Demographic variables, classification of incisional hernias according to the EHS(European Hernia Society), and complications after the intervention were recorded. Statistical analysis was performed with IBMSPSS-Statistics-25. Results: 13 patients were operated using TAR. Medium age was 56 years. 54% of patients were men and 46% women. Median BMI was 30. According to the EHS classification, the most frequent incisional hernia was M3(84.6%), followed by M4(61.5%) and M2(53.8%). W2(61.5%) and W3(30.8%). Median distance between the rectus in the CT prior the intervention was 85 mm. 100% had median laparotomy. 53.8% subcostal or stomal incision. 46% of the patients suffered some type of complication, 38.5% surgical. The complications were wound dehiscence secondary to skin necrosis(23%), abscess(15%), mesh infection(7%), hematoma(7%). Recurrence(7%). Subcostal or other laparotomy showed higher risk of complications of any type(p 0, 048). Distance between rectums was associated with high risk of skin necrosis and wound dehiscence(p 0, 015). No ileus, UTI, pneumonia, stroke or DVT. Conclusions: TAR is a technique used in complex abdominal wall with good results in relation to closure of hernia defect. However, in our cohort some postoperative complications were observed with a low rate of hernia recurrence. This highlights the effectiveness of TAR as a technique for complex abdominal wall closure.